The Impact of a National Intervention on Hospital-Acquired Bloodstream Infection Rates in Israeli Intensive Care Units. (4th October 2017) - Ben-David, Debby; Shitrit, Pnina; Rubinovich, Bina; Marchaim, Dror; Solter, Ester; Vaturi, Azza; Temkin, Elizabeth; Carmeli, Yehuda; Schwaber, Mitchell J
Abstract: Background: Hospital-acquired bloodstream infections and the subclass of central line-associated bloodstream infections (CLABSI) are associated with considerable morbidity, mortality, and healthcare costs. The burden of central line-associated bloodstream infections (CLABSI) in Israeli intensive care units (ICUs) has not been previously described. The present study aimed to assess the impact of implementing the NHSN practice recommendations for CLABSI prevention in Israeli ICUs. Methods: A prospective, national, ongoing interventional program was conducted from January 2012 until December 2016 in all adult and pediatric ICUs in Israel, The NHSN practice recommendations were introduced and implemented during 2012, including of insertion and maintenance bundles, education, outcome surveillance and feedback on CLABSI rates. The Israeli national nosocomial surveillance program is a mandatory, confidential system. Data on CLABSI and non CLABSI events were collected monthly. Feedback was disseminated to all hospitals twice yearly. Between January 2012 and December 2015, definitions were based on the 2012 NNIS/NHSN system; they were updated in 2016. Results: 114 ICUs in 30 hospitals contributed to 1, 727, 000 patient-days (PD). During the study period, a total of 6741 acquired BSI events were reported, 63% were non-CLABSI. In total, 2488 cases of CLABSI were observed over 447, 436 central line days (CLD). The pooled mean baseline total BSI and CLABSI rates were 5/1000 PD and 7.4/1000 CLD, respectively, and these decreased significantly to 3.3/ 1000PD ( P < 0.001) and 4/1000 CLD ( P < 0.001), respectively in 2016. (graph 1 and 2). Conclusion: Following a national intervention, significant decreases in both total BSI and CLABSI rates were observed. The large proportion of non-CLABSI BSI highlights the necessity to evaluate causes of non-CLABSI events and implement prevention measures. Disclosures: All authors: No reported disclosures.